Analysis of School Principals as Supervisors in the Implementation of Educational Supervision in Schools - Anggi Armadila, Viola Prisma; Usman, Ismail K; Ikhwan, Dien Majid (Jurnal Pendidikan Nusantara, 2025)
This study aims to analyze the role of school principals as supervisors in the implementation of educational supervision, with a focus on exploring the concept, functions, objectives, principles, and implementation of educational supervision in improving the quality of learning in schools. This research employs a qualitative method combined with a library research approach, where data were collected from primary and secondary sources, including scientific journals, books, and relevant articles, supplemented by direct observation at one of the schools. Data analysis was conducted using a content analysis technique through three sequential stages: data reduction, data display, and conclusion drawing and verification, with triangulation of sources applied to strengthen the validity and credibility of the findings by cross-validating data obtained from literature and field observations. The findings reveal that educational supervision has four key functions as a coordinator, consultant, team leader, and evaluator and the principal, as the central supervisor, holds a pivotal role in guiding educators to carry out their duties in accordance with educational standards. Effective supervision encompasses academic, administrative, and clinical supervision, with academic supervision contributing most significantly to improving teacher professionalism. The study also identifies twelve key supervisory responsibilities that principals must carry out systematically, while noting that implementation faces four main obstacles: cultural, regulatory, human resource, and infrastructure and funding challenges. It is concluded that the principal as supervisor plays a decisive role in shaping school culture, improving teacher performance, and ensuring that the teaching and learning process aligns with national education goals, as effective educational supervision guided by scientific, democratic, cooperative, and constructive-creative principles serves as a strategic instrument for achieving sustainable quality improvement in education.